2023
DOI: 10.3390/ijns9010009
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Congenital Adrenal Hyperplasia in Indian Newborns with Reflex Genetic Analysis of 21-Hydroxylase Deficiency

Abstract: Congenital adrenal hyperplasia (CAH), screened for in neonates, is the second most common endocrinopathy after congenital hypothyroidism.Newborn screening for CAH due to CYP21A2 deficiency is performed by immunologic assay for 17-hydroxyprogesterone (17-OHP). The second-tier test for confirmation of diagnosis is carried out on recall venous blood sample from screen positives measuring 17-OHP, or other metabolites of steroid metabolism by liquid chromatography–tandem mass spectroscopy. However, as steroid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Reviewing reports from 2020 until now, 2 multi-condition studies have been reported: a 3-year study of CH, CAH, G6PDD, GAL, and PKU in Bengaluru, South India [ 517 ]; and a Canadian collaboration study of CH, CAH, G6PDD, GAL, PKU and BIO in Udupi district of South India [ 518 ]. Reports continue regarding NBS for endocrinopathies: CH screening, prevalence, and etiology in Indian preterm babies [ 519 ]; a report of confirmatory testing from the original DBS to speed diagnosis of CAH (assuming that the DBS and patient match) [ 520 ]; a review of the challenges and opportunities resulting from NBS for CAH [ 521 ]; a case study of a newborn with unnecessary devastating consequences from CAH resulting from no NBS [ 522 ]; a standard operating protocol for routine NBS for CAH in Indian settings [ 523 ]; and a discussion of genetic confirmatory testing for CAH from the original DBS as a means of speeding the diagnostic process [ 520 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reviewing reports from 2020 until now, 2 multi-condition studies have been reported: a 3-year study of CH, CAH, G6PDD, GAL, and PKU in Bengaluru, South India [ 517 ]; and a Canadian collaboration study of CH, CAH, G6PDD, GAL, PKU and BIO in Udupi district of South India [ 518 ]. Reports continue regarding NBS for endocrinopathies: CH screening, prevalence, and etiology in Indian preterm babies [ 519 ]; a report of confirmatory testing from the original DBS to speed diagnosis of CAH (assuming that the DBS and patient match) [ 520 ]; a review of the challenges and opportunities resulting from NBS for CAH [ 521 ]; a case study of a newborn with unnecessary devastating consequences from CAH resulting from no NBS [ 522 ]; a standard operating protocol for routine NBS for CAH in Indian settings [ 523 ]; and a discussion of genetic confirmatory testing for CAH from the original DBS as a means of speeding the diagnostic process [ 520 ].…”
Section: Resultsmentioning
confidence: 99%
“…The risk can be much higher due to the high rates of consanguinity in the country. [ 55 ] Thus, genetic diagnosis in affected probands and carrier testing in their partners before planning pregnancy will be extremely beneficial. Continuous follow-up of both the partners being carriers or CAH-affected individuals marrying a carrier will benefit in better management of CAH-associated pregnancies and drastically reduce the incidence of CAH in India.…”
Section: Linical D Iagnosismentioning
confidence: 99%
“…To overcome the challenges with 17-OHP testing by LC-MS/MS, genetic testing for the most common mutations (screening for hotspot mutations) can be considered in those with elevated 17-OHP on first-line NBS with a turnaround time of 5–7 days. [ 55 ] This can be a suitable alternative for the second-tier LC-MS for accurate and cost-effective diagnosis of 21-OHD.…”
Section: Linical D Iagnosismentioning
confidence: 99%